Edukasi Pemanfaatan Sampah pada Siswa SMA di Sidoarjo: Limbah Serabut Kelapa sebagai Bahan Penguat pada Pembuatan Plastik Biodegradable - Fitri, Medya Ayunda; Said, Muhammad Husen; Aditya, Rizky; Azizah, Zahrotul; Fitrianah, Listin; Yafi, Muhammad Mansur; Hakim, Luqman (Journal of Science and Social Development, 2024)
Waste is one of the causes of environmental problems, especially plastic waste. Therefore, education is carried out regarding knowledge about waste and waste utilization to minimize the accumulation of plastic waste. The aim of this education is so that high school students have environmental awareness and are able to be creative in utilizing surrounding waste to make environmentally friendly products that have high economic value. This education was carried out using a presentation method regarding waste materials and examples of waste utilization, namely coconut fiber waste which has the potential to be used as a strengthening material in the manufacture of biodegradable plastic. The results of the education provided show that there has been an increase in understanding regarding waste and its use on the "sangat mengetahui" indicator of 86.67%.